Five autopsy reports of rib fractures in the mental hospital of Reggio Emilia (1874–5): pathogenesis proposal in defence of the 'non-restraint' system. Issue 3 (September 2021) - Tesi, Chiara; Picozzi, Mario
At the end of the nineteenth century, recurrent cases of rib fractures were recorded in psychiatric asylums, opening a long chapter of discussions about the application of the 'non-restraint' system. Here we present a brief discussion of an article written by Enrico Morselli about five cases of rib fractures in the mental asylum of Reggio Emilia, in 1874–5. Morselli, a supporter of the ideas of 'non-restraint', suggested a common pathological cause. His analysis proposed the osteomalacic condition as the possible cause of fractured ribs, rejecting the accusations of violence by asylum attendants. The discussion also examines similar cases of the same period, making rib fractures the means through which the issue of management of the insane was addressed.